Tahao/middle road from imagining nation to embodying transnation - Bobis, Merlinda (2016)
Access online through this link: https://www.plarideljournal.org/article/tahaomiddle-road-imagining-nation-embodying-transnation
Keywords: Tahao Road (Legazpi City); Multiculturalism